2010
DOI: 10.1007/s10803-010-1064-1
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Theatre as Therapy for Children with Autism Spectrum Disorder

Abstract: The pilot investigation evaluated a theatrical intervention program, Social Emotional NeuroScience Endocrinology (SENSE) Theatre, designed to improve socioemotional functioning and reduce stress in children with autism spectrum disorder (ASD). Eight children with ASD were paired with typically developing peers that served as expert models. Neuropsychological, biological (cortisol and oxytocin), and behavioral measures were assessed in a pretest–posttest design. The intervention was embedded in a full musical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
113
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(125 citation statements)
references
References 36 publications
8
113
0
4
Order By: Relevance
“…Some theater-based programs use theatrical techniques as a form of treatment for children with ASD [24][25][26]. For example, studies we have conducted have shown that SENSE Theatre ® , a theatrical intervention program in which youth with ASD learn a variety of acting techniques with peer actors who model communication and behavioral skills, contributes to significant changes in participants' social competence, communication, cognition, and interaction skills [27][28][29][30].…”
mentioning
confidence: 99%
“…Some theater-based programs use theatrical techniques as a form of treatment for children with ASD [24][25][26]. For example, studies we have conducted have shown that SENSE Theatre ® , a theatrical intervention program in which youth with ASD learn a variety of acting techniques with peer actors who model communication and behavioral skills, contributes to significant changes in participants' social competence, communication, cognition, and interaction skills [27][28][29][30].…”
mentioning
confidence: 99%
“…The authors concluded that the NCBRF's validity evidence was strong, and that the subscales of the ABC and the NCBRF that were thought to be related tap similar constructs. The factor structure of the NCBRF was established as evidence of its construct validity [28] and its psychometric properties have been independently evaluated and confirmed by several published studies [15,29,30] The NCBRF has also been widely used in published research investigating problem behavior in children with developmental disabilities [31][32][33][34] and has been translated/adapted into other languages [30,35]. The Isolate subscale of the NCBRF was of interest as an outcome measure as decreases in isolation would be an anticipated result of participation in the Hunter Heartbeat Method intervention.…”
Section: Nisonger Child Behavior Rating Formmentioning
confidence: 85%
“…Promising research from Corbett et al [15] on Social Emotional NeuroScience Endocrinology (SENSE) theatre offers support for this drama-based intervention's ability to improve socialemotional functioning and reduce stress in children with ASD. Research findings for a pilot study examining the efficacy of SENSE theatre indicate that participants showed some improvement in face identification and Theory of Mind skills [15]. Corbett et al [16] also assessed a 2 week summer camp model of the SENSE theatre program.…”
Section: Introductionmentioning
confidence: 99%
“…However, some described investigations evaluated adolescent social skills groups in school settings (Minihan et al 2011;Williams 1989) and other settings, such as on horseback (Gabriels et al 2012), at a musical theater company (Corbett et al 2011), in computer workshops (Wright et al 2011), and in summer camps (Lopata et al 2008). While most studies reviewed took place in the USA, several were conducted in other countries, such as Germany (Herbrecht et al 2009), Scotland (MacKay et al 2007), Ireland (Minihan et al 2011;Rose & Anketell 2009), Italy (Valenti et al 2010), and South Korea (Shin et al 2012).…”
Section: Settingmentioning
confidence: 99%
“…In another study, parents met with the group leaders three times over the course of the 11-month intervention to exchange information related to intervention progress and current difficulties (Herbrecht et al 2009). Several articles indicated the need to increase parent participation within the intervention process, with several proposing future inclusion of parent training components (e.g., Corbett et al 2011;Tse et al 2007). …”
Section: Generalization and Maintenance Techniquesmentioning
confidence: 99%